The changing industrial composition of manufacturing-based regions, 1980-2005 - Howard Wial (University of California, Institute of Urban and Regional Development (IURD), 2008)
The United States lost 4.5 million manufacturing jobs, about 24 percent of its manufacturing base, between 1980 and 2005. This loss, its causes, and its consequences for displaced workers and the nation as a whole, have been extensively studied and debated. Yet researchers have paid little attention to the kinds of jobs that have replaced the lost manufacturing jobs in manufacturingbased metropolitan areas that lost manufacturing jobs. These metropolitan areas, located primarily in the Great Lakes region, the Northeast, and the upper South, are the places in which the impacts of manufacturing job loss on the regional economy were, and generally still are, of greatest public concern. Policymakers in these regions need to understand how the industrial structures of their regional economies have changed if they are to craft effective industrylevel policies to rebuild those economies. Such policies may be designed either to accommodate the changes that have occurred or to alter the growth pattern of the regional economy.
Keywords: 330